Spanish Adaptation of the Organizational Culture Assessment Instrument: Reflection on the Difficulty in Transferring the ad hoc Factor - Assens-Serra, Jordi; Boada-Cuerva, Maria; Serrano-Fernández, María-José; Villajos, Esther; Boada-Grau, Joan (Frontiers in Psychology, 2021)
The Organizational Culture Assessment Instrument is a common instrument for measuring organizational culture in English-speaking countries based on four factors: Clan, ad hoc, Market and Hierarchy. However, to date, there is no proper translation of the scale into Spanish. In this study, we describe the translation and adaptation of the instrument through Exploratory Factor Analysis with a Spanish sample (n1 = 246; 69.9% men and 30.1% women) and Confirmatory Factor Analysis with a Peruvian sample (n2 = 510; 70.4% men and 29.6% women). The result reduces the four-factor internal structure to a three-factor structure that retains the Clan, Market and Hierarchy factors, but completely excludes the ad hoc factor. Confirmatory Factor Analysis shows acceptable indicators, reliabilities are good and indication of validity is also confirmed. In conclusion, this study has given rise to the instrument in Spanish, called OCAI-12, which is suitable for evaluating organizational culture.